Inter-observer agreement of color duplex ultrasound of central vein stenosis in hemodialysis patients. (October 2019) - Razek, Ahmed AKA; Khalek, Ahmed MA; Elwakeel, Hossam; Ebrahim, Moataz A
Purpose: To assess the inter-observer agreement of color duplex ultrasound of central vein stenosis in hemodialysis patients. Patients and methods: This prospective study was conducted on 35 hemodialysis patients with suspected central vein stenosis. All patients underwent color flow duplex examination of the subclavian, internal jugular and brachiocephalic veins in hemodialysis patients. Image analysis was performed by two reviewers for diameter reduction, peak venous velocity ratio, post-stenotic turbulent flow, waveform changes, and thrombus formation. Results: There was no significant difference between both observers for diameter reduction ( p  = 0.105) and for the mean peak systolic velocity ratio ( p  = 0.515). The overall inter-observer agreement of color duplex ultrasound of central vein stenosis was excellent ( k  = 0.84, percent agreement = 89.7%, P  = 0.001). There was excellent inter-observer agreement of both reviewers for diameter reduction ( k  = 0.928, percent agreement = 97.14%), peak venous velocity ratio ( k  = 0.7, percent agreement = 85.7%), waveform changes ( k  = 0.62, percent agreement = 77.14%), post-stenotic turbulent flow ( k  = 0.866, percent agreement = 88.6%), thrombus formation ( k  = 1, percent agreement = 100%). Conclusion: We concluded that color duplex ultrasound is a reliable and reproducible method for diagnosis of central vein stenosis in hemodialysis patients.